Investigation of an Active System of Reactive Power Compensation for Induction Motors - Zakis, J.; Rankis, I.; Zhiravetska, A. (Elektronika ir Elektrotechnika, 2006)
In the following paper there is analyzed possibility to change the power of compensation capacitors with thyristor regulated reactors. As an application of compensator asynchronous motor in steady-state regime is used. Using data from catalogues the usage of reactive power in asynchronous motor is researched. Charts that show changes of relative reactive power in different type asynchronous motors dependent on loading were acquired. Expressions for calculations of parameters of compensator have been also recommended. The required parameters of compensators are acceptable for operative compensation in steady state regime if load is changing. For process research computer modulation program PSIM is used. Using diagrams of phase current and voltage of the motor it is concluded that compensation effectively reduces network current especially in no-load operation. Ill. 5, bibl. 2 (in English; summaries in English, Russian and Lithuanian).